Die Anomaloninae der Sammlung Arnold Förster - Typenrevision und faunistische Anmerkungen (Hymenoptera, Ichneumonidae). - Schnee, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 2008)
The 22 species of the subfamily Anomaloninae described by Förster are revised. Only the following five species have proved to be valid: Barylypa propugnator (Förster, 1855), Barylypa mesozona (Förster, 1878), Erigorgus melanops (Förster, 1855), Erigorgus foersteri (Mocsáry, 1897) (a replacement name for Anomalon brevicorne Förster, 1855) and Atrometus insignis (Förster, 1878). Lectotypes are designated for seven species. 16 new synonymies are established. In the remaining Förster collection 41 species were found. They are briefly annotated faunistically and in view of their host relationships.KeywordsFörster collection, Anomaloninae, type revision, faunistics.Nomenclatural Actsaggressorium Förster, 1860 (Agrypon), Lectotype; syn. n. of Agrypon flaveolatum (Gravenhorst, 1807)brachypterum Förster, 1860 (Agrypon), Lectotype; syn. n. of Agrypon clandestinum (Gravenhorst, 1829)clandestinum Förster, 1860 (Agrypon), syn. n. of Agrypon clandestimum (Gravenhorst, 1829)cognatum Förster, 1860 (Agrypon), syn. n. of Agrypon varitarsum (Wesmael, 1849)confusum Förster, 1860 (Agrypon), Lectotype; syn. n. of Agrypon flaveolatum (Gravenhorst,1807)elegantulum Förster, 1860 (Agrypon), Lectotype; syn. n. of Agrypon flaveolatum (Gravenhorst, 1807)furtivum Förster, 1860 (Agrypon), syn. n. of Agrypon anomelas (Gravenhorst, 1829)melanomerum Förster, 1860 (Agrypon), Lectotype; syn. n. of Camposcopus nigricornis (Wesmael, 1849)rubricatum Förster, 1860 (Agrypon), Lectotype; syn. n. of Agrypon flaveolatum (Gravenhorst, 1807)serpentinum Förster, 1860 (Agrypon), Lectotype; syn. n. of Agrypon batis (Ratzeburg, 1852)subclavatum Förster, 1860 (Agrypon), syn. n. of Agrypon flexorium (Thunberg, 1822)carinatum Brischke, 1880 (Anomalon), syn. n. of Barylypa propugnator (Förster, 1855)longicorne Brauns, 1895 (Anomalon), syn. n. of Barylypa mesozona (Förster, 1878)rufum Habermehl, 1920 (Anomalon), Lectotype; syn. n. of Barylypa propugnator (Förster, 1855)rubricatus Förster, 1878 (Atrometus), syn. n. of Agtrometus insignis Förster, 1878frisiaca Habermehl, 1922 (Barylypa), syn. n. of Barylypa mesozona (Förster, 1878)insidiator Förster, 1878 (Laphyctes), syn. n. of Barylypa propugnator (Förster, 1855)